Pengaruh Perendaman Bambu Dengan Air Laut Terhadap Kekerasan dan Laju Keausan Komposit Kampas Rem - Sunardi Sunardi; Hermawan Susanto; Rina Lusiani; Iman Saefuloh; Hamdan Akbar Notonegoro; Moh. Fawaid (TURBO [Tulisan Riset Berbasis Online], 2023)
Bamboo is a natural material that is widely found in South Banten. Using bamboo as an alternative material for manufacturing brake pads is interesting to research. Bamboo resistance to attacks of organisms is so low that it is necessary to give initial treatment. Preservation of bamboo sticks is done by soaking them in seawater. This immersion is determined for 15 and 30 days. The comparison of the composite constituent composition is 30% bamboo fiber, 28% bamboo particles, 2% zinc, and 40% epoxy resin. Compaction pressure is carried out by 400 kg/cm2 for 10 minutes. The sintering process is carried out at a temperature of 150 °C for 60 minutes. From this research, it is known that the immersion of bamboo stems in seawater tends to decrease the hardness and the wear rate of composites.